Neurological deficits are present in syndromic craniosynostosis patients with and without tonsillar herniation. (September 2020) - Doerga, P.N.; Rijken, B.F.M.; Bredero-Boelhouwer, H.; Joosten, K.F.M.; Neuteboom, R.F.; Tasker, R.C.; Dremmen, M.H.G.; Lequin, M.H.; van Veelen, M.L.C.; Mathijssen, I.M.J.
Abstract: Background: Children with syndromic craniosynostosis (sCS) have a higher incidence of cerebellar tonsillar herniation (TH) than the general population. In the general population, TH ≥ 5 mm below the foramen magnum is associated with typical neurological deficits but, in sCS, we do not know whether this degree of TH is required before such deficits occur. Objective: This prospective cohort study aimed to determine the association between findings on neurological assessment and cerebellar tonsillar position. Methods: Magnetic resonance imaging (MRI) was used to determine TH ≥ 5 mm and the presence of syringomyelia. In regard to the outcome of neurological deficits, these were categorized according to: A, cerebellar function; B, cranial nerve abnormalities; and C, sensory or motor dysfunction. Results: Twenty of 63 patients with sCS (32% [95% confidence interval 21–45%]) had TH ≥ 5 mm and/or syringomyelia. There was no significant difference in proportion between individual forms of sCS: 16/34 Crouzon, 2/11 Muenke, 2/12 Apert, and 0/7 Saethre-Chotzen patients. Neurological deficits were prevalent (73% [95% confidence interval 60–83%]), and as frequent in patients with TH ≥ 5 mm and/or syringomyelia as those without. Surgery occurred in 3 patients overall, and only in Crouzon patients. Conclusion: Determining the effect of TH ≥ 5 mm on neurologic functioning in sCS patients is used to better determine when surgical intervention is warranted. However, we have found that neurological deficits are prevalent in sCS patients, irrespective of cerebellar tonsillar position, suggesting that such findings are developmental and, in part, syndrome-specific central nervous system features. Highlights: Neurological deficits are highly prevalent in syndromic craniosynostosis. Absence of neurological deficits does not rule out cerebellar tonsillar herniation. Surgery because of cerebellar position and/or syringomyelia is rarely needed.